Do Political Connections Affect Firm Performance? Evidence from a Developing Country. Issue 8 (2nd August 2016) - Saeed, Abubakr; Belghitar, Yacine; Clark, Ephraim
ABSTRACT: We investigate how politicians serving on the boards of directors influence firm performance. The results show a negative relationship between political connections and firm performance. Specifically, politically connected firms underperform nonconnected firms directors by almost 17 percent and 15 percent based on return on assets and return on equity, respectively. By stratifying the sample duration into two periods based on the political environment, we find that this effect is more pronounced in autocratic as opposed to democratic regimes. Finally, our results also suggest that the performance of connected firms with more growth opportunities is not affected by political connections.